PERAN KLASTER PARIWISATA TERHADAP EKONOMI KREATIF KABUPATEN BANYUWANGI DI ERA INDUSTRI 4.0 - Satria, Dias; Maharani Wibowo, Joshi (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
Banyuwangi Regency is one city in Indonesia with a high potential in the tourism sector and is famous for its main attraction, Ijen Crater National Park or more known as Ijen Crater. In 2019, this destination was appointed as the center of the tourism cluster area by utilizing local potential to support regional economic growth. This research was conducted to determine the tourism clusters’ role in supporting the creative economy by applying technology 4.0 in Banyuwangi Regency. The result showed that the tourism cluster policy application positively encourages local communities to be more creative and innovate, like creating new SME featured products by utilizing the existing biodiversity and local wisdom nearby. Unfortunately, the development of the creative industry business in the Kawah Ijen cluster have some obstacles, caused by social, financial, and infrastructure factors. To overcome that obstacle, this research also tries to provide recommendation policy suggestions in the form of local community inventions that integrate local community institutions and technology 4.0 to overcome the negative impact. The related stakeholder can create a digital-based ecosystem to motivate local people to continue being innovative and creative.